Analysis of Bankruptcy Prediction Models in Determining Bankruptcy of Consumer Goods Companies in Indonesia - Thomas, Gen Norman; Indriaty, Lely (International Journal of Psychosocial Rehabilitation, 2020)
– this study aimed at analyzing three different bankruptcy prediction models: the Altman model, the Grover model and the Zmijewski model in predicting bankruptcy in the public consumer goods: sub-sector food and beverage. the reseacher took data in the form of financial statements from the Indonesia Stock Exchange in 2015- 2018. there were 11 sample companies selected using the purposive sampling method. The research found that the Altman Z score model got an accuracy rate of 47.7% score against bankruptcy predictions ; whereas, the Grover G model and the Zmijewski X model got an accuracy rate of 100% score against bankruptcy predictions. In addition, the result of the analysis of ALTO and companies in the gray area position proved that the Altman Z score is also not feasible. Therefore, the study concluded the Grover G model and the Zmijewski Model are the most significant bankruptcy prediction models to use in predicting bankruptcy of public companies consumer goods: sub-sector food and beverage in Indonesia. It implied to the public companies consumer goods: sub-sector food and beverage in Indonesia in order to choose the appropriate bankruptcy prediction models to achieve the maximum accuracy.